IMPROVEMENT OF LEARNING OUTCOMES OF GRADE VIII STUDENTS OF SMPN 4 SALATIGA THROUGH THE PBL MODEL WITH A CRT APPROACH - Dewi, Riana; Pratama, Fika Widya; Setiawan, Adi; Deswita, Yenny (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
This study aims to improve the mathematics learning outcomes of class VIII G students of SMP Negeri 4 Salatiga in the material Surface Area of Flat Sided Buildings through the PBL (Problem Based Learning) model with the CRT (Culturally Responsive Teaching) approach. This research is classroom action research conducted in two cycles using the Kemmis and MC Taggart models with 4 stages namely planning, implementation, observation/observation, and reflection. The subjects of this study were class VIII G students of SMP Negeri 4 Salatiga for the 2022/2023 academic year, consisting of 30 students (15 boys and 15 girls). The technique of collecting data in this research uses observation sheets of the implementation of learning and learning achievement tests. The criteria for the success of learning outcomes in this study were increasing the class average score in each cycle and the class achieving classical mastery (many students who completed individually  85%). The results of this study showed an increase in class average scores from pre-cycle to cycle 1 (from 62.7 to 77.03) and cycle 1 to cycle 2 (from 77.03 to 84.1) and the achievement of classical mastery of 86. 67%. The conclusion obtained in this study is that the application of the PBL model with the CRT approach has succeeded in increasing the mathematics learning outcomes of class VIII G students of SMP Negeri 4 Salatiga on the material surface area of flat side shapes.